The effectiveness of foreign direct investment study case in Iskandar Region Development Authority (IRDA) / Ismail Abdul Kadir Ishak - Ishak, Ismail Abdul Kadir (Faculty of Business and Management, 2011)
This is a study on “The Effectiveness of Foreign Direct Investment” case study in Iskandar Region Development Authority (IRDA). Foreign direct investments are the most important for the company because the investor can easily made any business with that company. In this study, it will discuss the role of IRDA towards the foreign direct investments on how they attract the investors to come over Iskandar Malaysia to invest. The programs that organize by IRDA are the way how the role of IRDA to attract foreign direct investment. The total of foreign direct investment in Iskandar Malaysia show that the development of Iskandar Malaysia needs them because investors can generate more profit to both investors and Iskandar Malaysia as well as the year to year increasing the total number of investors since 2006 until now. There is prove shows that no slowing of foreign direct investments in Iskandar Malaysia which this statement are stated by our Prime Minister, Datuk Seri Najib Tun Razak. Interview session had been made with Chief Executive of Iskandar Region Development Authority (IRDA) regarding the foreign investment in Iskandar Malaysia and the feedback is positive because from year to year, investment in Iskandar Malaysia is keep increase. Recommendation regarding on how to improve and attract investors to come and invest in Iskandar Malaysia has been recommend to IRDA where the result regarding that matters are between me and Assistant Vice President of Economics and Businesses in IRDA.